Characterizing functional connectivity gradients for the hippocampus–amygdala complex in healthy and psychiatric cohorts - Xiang-Shen Liu; Janna N. Vrijsen; Linlin Yan; Koen V. Haak; Rose M. Collard; Philip F. P. van Eijndhoven; Christian F. Beckmann; Guillén Fernández; Indira Tendolkar; Nils Kohn (Brain Structure and Function, 2026)
The hippocampus and amygdala play essential roles in human cognition and emotion, through their extensive connectivity with other brain regions and close interaction between them. Uncovering the functional organization of the hippocampus–amygdala complex and its relationship with neurotransmitter distribution can enhance our understanding of their biological functionality, and provide a basis for further exploration of the clinical relevance. An emerging functional connectivity analysis method termed connectopic mapping, may offer a novel approach to characterize this functional organization. In this study, we applied connectopic mapping to the hippocampus-amygdala complex, testing its utility with resting-state functional magnetic resonance imaging (fMRI) scans of two independent datasets: one comprising healthy individuals ( N = 410) and another comprising a psychiatric cohort ( N = 367). The spatial organization of derived gradient maps was compared to 18 positron emission tomography (PET) or single photon emission computed tomography (SPECT) scan templates for different neurotransmitter systems. Individual gradient–neurotransmitter similarity indices were correlated with mental health outcomes. Our analyses identified six distinct gradient maps in both datasets. The third-order gradients showed stable similarity with 5-HT1A receptor maps across various resting-state scans. Similarities were also observed between gradient maps and the distribution patterns of neurotransmitters within the dopaminergic system. Individual gradient-to-5-HT1A similarity was positively correlated with depressive severity and anxiety sensitivity, highlighting the psychopathological relevance. These findings demonstrate that across the psychiatric continuum, connectopic mapping is a powerful tool for exploring the relationship between functional connectivity organization and neurotransmitter distribution, showing potential as a comprehensive transdiagnostic biomarker.